2022
DOI: 10.3389/fnagi.2022.814893
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Volume-Wise and Voxel-Wise Concordance Among Dynamic Intrinsic Brain Activity Indices in Parkinson’s Disease: A Resting-State fMRI Study

Abstract: Researches using resting-state functional magnetic resonance imaging (rs-fMRI) have applied different regional measurements to study the intrinsic brain activity (IBA) of patients with Parkinson’s disease (PD). Most previous studies have only examined the static characteristics of IBA in patients with PD, neglecting the dynamic features. We sought to explore the concordance between the dynamics of different rs-fMRI regional indices. This study included 31 healthy controls (HCs) and 57 PD patients to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Some studies also found that the symptom severity of PD significantly correlated with such abnormal variability in the visual and sensorimotor regions. 49,50 We speculate that if abnormal signal variability in these regions indicates more random activity of the brain and then result in weaker autocorrelation, which can be interpreted the current findings. Moreover, abnormal intrinsic timescales in multisystem also refer to abnormal functional hierarchy of the brain in individuals with PD.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Some studies also found that the symptom severity of PD significantly correlated with such abnormal variability in the visual and sensorimotor regions. 49,50 We speculate that if abnormal signal variability in these regions indicates more random activity of the brain and then result in weaker autocorrelation, which can be interpreted the current findings. Moreover, abnormal intrinsic timescales in multisystem also refer to abnormal functional hierarchy of the brain in individuals with PD.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings showed abnormal temporal property of local neural activity in the visual, sensorimotor, and cognitive systems in PD, which was consistent with the previous studies. For example, the previous fMRI studies that calculated the variability of brain signal across time found abnormal variance in visual [47][48][49] , sensorimotor 47,50 , and frontal 51,52 regions in PD. Some studies also found that the symptom severity of PD significantly correlated with such abnormal variability in the visual and sensorimotor regions.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of the voxel-based analysis were reported with a combined threshold of vertexwise p < 0.05 and a clusterwise p < 0.05 after a correction for multiple comparisons using Gaussian random field theory. 31…”
Section: Methodsmentioning
confidence: 99%
“…Although the rs-fMRI was collected in a quiet state of the subjects, the brain activity fluctuated with time ( Kong et al, 2021 ). Dynamic DC (dDC) is a method combines sDC with “sliding window” ( Tian et al, 2022 ), reflecting the time dynamics of remote functional connectivity ( Du et al, 2021 ). Although dDC has not been reported in TN, it has been applied to Parkinson’s disease ( Wang et al, 2022 ), major depressive disorder (MDD) ( Yang et al, 2022 ), schizophrenia ( Wang et al, 2021 ), depressive mania ( Sun et al, 2022 ), and other diseases.…”
Section: Introductionmentioning
confidence: 99%